Significance of Critical Thinking through Education in Countering Violent Extremism in Pakistan - Muhammad Ansar Naseer; Ghazala Shaheen (International Journal of Multidisciplinary Sciences and Arts, 2023)
Pakistan is not an exception to the severe problem that violent extremism poses to nations worldwide. This article examines how important education is in preventing violent extremism and promoting a more accepting and inclusive society. Education gives people the skills they need to reject extremist beliefs and look for peaceful ways to resolve disputes by encouraging critical thinking, religious and cultural tolerance, and civic ideals. The article evaluates current programs in Pakistan, including the "Sabawoon Rehabilitation Center," which is run by the Pakistan Army, and cites successful educational initiatives from other nations. In order to guarantee the efficacy of educational programs, monitoring and assessment become essential elements. Stakeholders can optimize the impact of their contributions by defining clear indications of success and fostering a culture of continual development. The document ends with a call to action, calling all parties involved—including government organizations, civil society groups, religious institutions, educators, and communities—to prioritize and fund education as a long-term preventive measure against violent extremism in Pakistan. A more robust and peaceful society can be created by combining efforts and strengthening minds via education, paving the road for a better future.